THE PHONETIC DIVERSITY OF ENGLISH SPEECH STYLES - Fayzulloyeva Zilola Zafarovna,; Majidova Mohigul, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: The phonetic features of various speech styles in the English language not only enrich the linguistic landscape but also serve as vital markers of identity, social status, and cultural heritage, urging us to embrace this diversity as a reflection of our shared humanity. In the multifaceted world of English, phonetic features play a crucial role in shaping how we communicate, express identity, and connect with others. From the crisp enunciation of Received Pronunciation (RP) to the melodic intonations of African American Vernacular English (AAVE) and the regional accents that characterize varieties of English in the United States and the United Kingdom, these speech styles represent meaningful sociolinguistic variation rather than simple pronunciation differences [1].